Penggunaan Metode Permainan Tradisional Petak Jongkok Dalam Meningkatkan Perkembangan Sosial Emosional Anak di RA Nurul Ilmi Arrafi - Alifia Sitta Ramadhani; Sri Wahyuni (EduInovasi: Journal of Basic Educational Studies, 2023)
This research in motivated by observational data wich shows that Social Emotional development in group A RA Nurul Ilmi Arrafi Kec. Medan Polonia Kel. Sari Rejo is still said that not all of them have developed very well. To help improve social emotional development the researchers made a game of squatting hide. The formulation of the problem in this research is whether the game of squatting hide can improve social emotional development in group A children in group A as subject. The study wa conducted in 2 cycles. The results showed that in the preaction the average value of children’s social emotional development wa still 5.4 after the action cycle I the average value of children began to increase to 7.2 and in the last cycle II the average value of children increased to 9.7. this shows that squatting hide games can improve children’s Social Emotional development. Keywords: Social Emotional Development,Squatting Hide Game.